Real-time response counterattack strategy of tolerant microalgae Chlorella vulgaris MBFJNU-1 in original swine wastewater and free ammonia. (June 2023) - Dai, Jingxuan; Zheng, Mingmin; He, Yongjin; Zhou, Youcai; Wang, Mingzi; Chen, Bilian
Graphical abstract: Highlights: Resistance mechanism of microalga in original swine wastewater (OSW) was illustrated. The stress of OSW and free ammonia (FA) by microagla was analyzed by transcriptomics. Correlation analysis verified that OSW and FA had the similar effects on microalgae. Significant down-regulated in galactose and nitrogen metabolism was found by stress. Important up-regulated in glycolysis, photosystem and glutathione pathways was shown. Abstract: This work was the first time to systematically clarify the potential tolerance mechanism of an indigenous Chlorella vulgaris MBFJNU-1 towards the free ammonia (FA) during the original swine wastewater (OSW) treatment by transcriptome analysis using C. vulgaris UETX395 as the control group. The obtained results showed that C. vulgaris MBFJNU-1 was found to be more resistant to the high levels of FA (115 mg/L) and OSW in comparison to C. vulgaris UETX395 (38 mg/L). Moreover, the transcriptomic results stated that some key pathways from arginine biosynthesis, electron generation and transmission, ATP synthesis in chloroplasts, and glutathione synthesis of C. vulgaris MBFJNU-1 were greatly related with the OSW and FA. Additionally, C. vulgaris MBFJNU-1 in OSW and FA performed similar results in the common differentially expressed genes from these mentioned pathways. Overall, these obtained results deliver essential details in microalgal biotechnology to treat swine wastewater and high free ammonia wastewater.